The effect of different extraction methods on the chemical composition of Eurycoma Longifolia jack (Tongkat Ali) root extract - Faisal, Ghasak Ghazi; Najmuldeen, Ghazi Faisal; Kamalanathan, Narayanan; Kirubananthan, Deeveeya (2019)
Extracting essential oils from plants require an efficient method. Currently, different methods of extraction are used to extract the roots of Eurycoma longifolia jack. Each extraction method affects the yield and composition of the extract produced. In this study we compared three different extraction methods ; Microwave Assisted Extraction (MAE), Soxhlet Extraction (SE) and Conventional Steam Extraction (CSE). The extract obtained was characterized using gas chromatography mass spectroscopy (GC-MS) by comparing the compositions of components present in commercial Tongkat Ali oil stored in the GC-MS library. The findings showed that the MAE gives a maximum yield percentage of 5 % with six chemical components extracted in 20 min while SE and CSE gives high yield percentage of 28.3% in 3 hours and 2.5 % in 6 hours respectively with only three chemical components extracted. Therefore, MAE is the optimum method for extracting essential oil from Tongkat Ali with a high quality and short duration.